Development of an automated home-based aquaponics system - Hamed Ghazal, Abdullah Hazem; Sophian, Ali (2017)
The Aquaponics systems, a path to sustainable development is aimed at forging a business-like mentality in order to meet the basic needs to contribute to the multifaceted development of communities, both urban and rural, in turn allowing the strengthening of knowledge curiosity, ingenuity and creativity from the question as a starting point of all research on self gardening systems at homes. This paper outlines the aquaponics technology as a replacement of traditional gardening at homes as well as the features that Mechatronics engineers can implement in such technology. It can be defined as a combination between two production lines, Hydroponics in charge of growing plants and Aquaculture in charge of growing fish that through a symbiotic process complement one another. Overall idea is to generate a system in which organic waste water produced by fish -an aquatic body- are converted through bacterial action on nitrates, which serve as food source for plants. This cycle is being performed as water is pumped from the fish tank to the growing bed, plants, then a bell-siphon draining mechanism is in charge of getting the filtered back into fish tank. The Aquaponics as an educational tool applicable for home use is a system that can be used in different areas of science to increase the interest of paterfamilias in having such technology in hands as a source of organic food production and business. IOT is added to notify the user.